About some economic and legal basis for successful development of a green economy (Eurasian Journal of Ecology, 2016)
Economic and legislative conditions under which it is possible the successful development of renewable energy sources in Kazakhstan are considered.
Keywords: Alternative energy; green economy; innovation; forecast of electricity consumption; reducing greenhouse gas emissions.